New information on Stokesosaurus, a tyrannosauroid (Dinosauria: theropoda) from North America and the United Kingdom - Benson, R (2008)
A partial postcranial skeleton from the Late Jurassic (Tithonian) of Dorset, England represents a new species of the theropod dinosaur Stokesosaurus, Stokesosaurus langhami. S. langhami is a member of Tyrannosauroidea, showing a distinct median vertical ridge on the lateral surface of the ilium, a prominent shelf medial to the preacetabular notch, a pronounced ischial tubercle, and a tibia that is elongate relative to the femur. One of only two definitive Jurassic tyrannosauroids known from more than isolated elements, it is the largest Jurassic tyrannosauroid reported to date and provides additional evidence for the presence of relatively small- or medium-sized basal tyrannosauroids in Asia, North America, and Europe during the Late Jurassic. The occurrence of Stokesosaurus in the Tithonian of the UK and USA and the absence of tyrannosauroids in contemporaneous west African faunas supports the hypothesis of a paleobiogeographic link during the Late Jurassic between North America and Europe, to the exclusion of Africa. © 2008 by the Society of Vertebrate Paleontology.